1990
DOI: 10.7326/0003-4819-112-9-678
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine in Decompensated, Treatment-Refractory Noninsulin-Dependent Diabetes Mellitus

Abstract: Combining antidiabetic therapy with hydroxychloroquine in decompensated, treatment-refractory patients with noninsulin-dependent diabetes may help to break the vicious circle of hyperglycemia and lead to better management of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 12 publications
2
92
1
5
Order By: Relevance
“…14 Antimalarials also have been shown to lower glycated hemoglobin levels in patients with type 2 diabetes who have suboptimal glucose control. 12 In addition, the prevalence of diabetes in patients with rheumatoid arthritis is similar to that of other patients, even though patients with rheumatoid arthritis are more sedentary and often treated with corticosteroids that induce weight gain. 15,16 This study was designed to investigate the association between hydroxychloroquine therapy and risk of incident diabetes in patients with rheumatoid arthritis.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…14 Antimalarials also have been shown to lower glycated hemoglobin levels in patients with type 2 diabetes who have suboptimal glucose control. 12 In addition, the prevalence of diabetes in patients with rheumatoid arthritis is similar to that of other patients, even though patients with rheumatoid arthritis are more sedentary and often treated with corticosteroids that induce weight gain. 15,16 This study was designed to investigate the association between hydroxychloroquine therapy and risk of incident diabetes in patients with rheumatoid arthritis.…”
mentioning
confidence: 81%
“…24,25 Antimalarial agents have been reported to cause both symptomatic and asymptomatic hypoglycemia. 10,12,13,26 Antimalarials also have been explored as an adjunct to insulin and oral hypoglycemic agents for poorly controlled type 2 diabetes. 12,26 Patients with non-insulindependent diabetes with suboptimal disease control during an intensive outpatient intervention showed an absolute reduction in glycated hemoglobin A 1c level of 3.3% when treated for 6 months with hydroxychloroquine dosed at 200 mg 3 times per day.…”
Section: Commentmentioning
confidence: 99%
“…Methotrexate is thought to exert its effects through its anti-inflammatory action mediated through adenosine 60 which is known to enhance glucose metabolism through insulin and alters lipid metabolism. 61 Anti-TNF-α drugs have been shown to improve insulin resistance and insulin sensitivity 59 apart from decreasing inflammation while hydroxychloroquine decreases blood glucose levels 62 and total cholesterol levels. 63 But well designed studies comparing the prevalence of MetS in patients with RA on treatment with disease modifying antirheumatic drugs (DMARDs) and those who are treatment naïve are lacking.…”
Section: Rheumatoid Arthritis Metabolic Syndrome and Cardiovascular mentioning
confidence: 99%
“…10 (Table 5) Another study by Quatraro et al showed decreased insulin requirements in diabetic patients receiving HCQ with the C peptide levels remaining the same. 16 Inhibitory effect on insulin metabolism in animal models and in vitro studies have also been documented with evidence of decreased degradation and intracellular accumulation. 14,15,17 Chloroquine analogues have plasma lipid-lowering effects in diabetes mellitus, RA, SLE and dyslipidaemia that are therapeutically relevant due to the increased risks of premature atherosclerosis in these diseases.…”
mentioning
confidence: 99%